2019
DOI: 10.1021/acs.jmedchem.9b00959
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Boundaries of Molecular Representation for Drug Discovery with the Graph Attention Mechanism

Abstract: Hunting for chemicals with favorable pharmacological, toxicological, and pharmacokinetic properties remains a formidable challenge for drug discovery. Deep learning provides us with powerful tools to build predictive models that are appropriate for the rising amounts of data, but the gap between what these neural networks learn and what human beings can comprehend is growing. Moreover, this gap may induce distrust and restrict deep learning applications in practice. Here, we introduce a new graph neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
616
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 638 publications
(726 citation statements)
references
References 39 publications
3
616
0
Order By: Relevance
“…Recently, a GNN method: Attentive FP, has gained increasing attention from the scientific community. [28] As shown in Table 1, Attentive FP yields the best predictions to 6 out of 11 benchmark datasets, including 2 regression tasks (ESOL and FreeSolv) and 4 classification tasks (MUV, BBBP, ToxCast and ClinTox), highlighting its impressive performance in modelling a variety of chemical properties in comparison with several other graph-based methods. A majority of those studies claimed that graph-based models are typically superior or comparable to traditional descriptor-based models, [25,[31][32][33][34][35][36] and only a few studies gave the opposite conclusions.…”
Section: For Table Of Contents Use Only Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Recently, a GNN method: Attentive FP, has gained increasing attention from the scientific community. [28] As shown in Table 1, Attentive FP yields the best predictions to 6 out of 11 benchmark datasets, including 2 regression tasks (ESOL and FreeSolv) and 4 classification tasks (MUV, BBBP, ToxCast and ClinTox), highlighting its impressive performance in modelling a variety of chemical properties in comparison with several other graph-based methods. A majority of those studies claimed that graph-based models are typically superior or comparable to traditional descriptor-based models, [25,[31][32][33][34][35][36] and only a few studies gave the opposite conclusions.…”
Section: For Table Of Contents Use Only Introductionmentioning
confidence: 92%
“…To well compare the performance of descriptor-based and graph-based models, the dataset collection related to drug discovery used by Attentive FP was also adopted in this study. [28] This dataset collection contains 11 different datasets originally reported in MoleculeNet for a variety of chemical endpoints. [33] In the study reported by Xiong et al, [28] the molecules that could not be successfully processed by RDKit [44] or the Attentive FP model were excluded from the original datasets.…”
Section: Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the DL, the features within an image are extracted by a convolution process with CNNs. Therefore, by specifying the convolutional region(s) using combination analysis with other, new methods to visualize the region(s) of the feature(s) (Selvaraju et al, 2016;Xu et al, 2017;Farahat et al, 2019;Oh et al, 2019;Xiong et al, 2019), the important part or area of the chemical structure necessary for prediction model construction could be estimated. Secondly, the optimal 3Dstructuring rules have not been defined.…”
Section: Comparison Of the Predictionmentioning
confidence: 99%